2021
DOI: 10.1108/jhr-02-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking for mental health concerns: review of Indian research and emergent insights

Abstract: PurposeThe purpose of this review was to examine Indian research on help-seeking for mental health problems in adults.Design/methodology/approachOriginal Indian research studies on help-seeking for mental health, published from the year 2001−2019 were searched on PubMed, EBSCO, ProQuest and OVID using a set of relevant keywords. After applying exclusion criteria, 52 relevant research studies were identified.FindingsThe reviewed studies spanned a variety of themes such as barriers and facilitators to help-seeki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 68 publications
(111 reference statements)
2
2
0
Order By: Relevance
“…Furthermore, Arabs across countries have negative attitudes towards formal help-seeking, reluctance to seek help, and preferred informal sources of psychological support. These findings are consistent with help-seeking attitudes in Filipino [ 11 ], Asian American [ 112 ], and Indian ethnic minority populations [ 113 ]. Differences in help-seeking attitudes among Arabs from different countries is not thoroughly addressed in existing literature, and only one study found differences [ 45 ], while another did not [ 47 ].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, Arabs across countries have negative attitudes towards formal help-seeking, reluctance to seek help, and preferred informal sources of psychological support. These findings are consistent with help-seeking attitudes in Filipino [ 11 ], Asian American [ 112 ], and Indian ethnic minority populations [ 113 ]. Differences in help-seeking attitudes among Arabs from different countries is not thoroughly addressed in existing literature, and only one study found differences [ 45 ], while another did not [ 47 ].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, Arabs across countries have negative attitudes towards formal help-seeking, reluctance to seek help, and preferred informal sources of psychological support. These ndings are consistent with help-seeking attitudes in Filipino (11), Asian American (112), and Indian ethnic minority populations (113). Differences in help-seeking attitudes among Arabs from different countries is not thoroughly addressed in existing literature, and only one study found differences (45), while another did not (47).…”
Section: Discussionsupporting
confidence: 75%
“…School-age adolescents tend to choose formal services such as seeing a doctor or professional staff. Therefore, knowledge and self-efficacy play an important role in changing help-seeking behavior (Sanghvi, 2022).…”
Section: Introductionmentioning
confidence: 99%